Recent vegetable varieties from ICAR-II VR, Varanasi - Singh, P M; Rai, N; Bhardwaj, D R; Kumar, Rajesh; Pandey, S; Chaubey, T; Singh, B K; Tiwari, S K; Reddy, Y S; Karmakar, P; Reddy, B R; Vidyasagar; et al. (Indian Horticulture, 2023)
With the increasing awareness about importance of vegetables for nutritional security, their demand is also increasing very fast, but due to burgeoning population it is not feasible to increase the area proportionately. The enhancement of productivity is the option to meet this fast increasing demand. Development of improved vegetable varieties is imperative to meet the increasing demand and for diversifying the vegetable basket. In view of this, the Indian Institute of Vegetable Research, Varanasi has constantly been working to develop improved varieties in various vegetable crops.